Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1540-8159.1993.tb01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Measuring Relative Right Ventricular Volumes and Ejection Fraction with Implantable Rhythm Control Devices

Abstract: Ejection fraction (EF), the ratio between stroke volume (SV) and end-diastolic volume (EDV), is a valuable contractility indicator. Unlike SV, the Frank-Starling effect is automatically compensated in the calculation of EF. It was the aim of this study to evaluate the physiological behavior of impedance derived measurements of relative right ventricular (RV) volumes and EF, obtained with standard pacing leads. Seven patients were evaluated at the time of pacemaker implant or replacement. Since no absolute stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…These calibration steps are necessary to obtain absolute values of ventricular volume. As this calibration is not possible in an implantable device, only relative measurements of volume are possible in a pacemaker system, and, although studies using stroke volume for closed-loop control of stimulation have been performed (SALO et at., 1984;CHIRIFE, 1991;CHIRIFE et at., 1993), no such pacemaker systems are commercially available at the present time. Absolute values of volume can be very difficult to measure, if possible at all, although some non-invasive instruments are available on the market.…”
Section: Medical and Biological Engineering And Computing 2002 Vol 40mentioning
confidence: 94%
“…These calibration steps are necessary to obtain absolute values of ventricular volume. As this calibration is not possible in an implantable device, only relative measurements of volume are possible in a pacemaker system, and, although studies using stroke volume for closed-loop control of stimulation have been performed (SALO et at., 1984;CHIRIFE, 1991;CHIRIFE et at., 1993), no such pacemaker systems are commercially available at the present time. Absolute values of volume can be very difficult to measure, if possible at all, although some non-invasive instruments are available on the market.…”
Section: Medical and Biological Engineering And Computing 2002 Vol 40mentioning
confidence: 94%
“…Several attempts have bccn rcported to achieve this goal using right ventricular impcdancc mcasurcinents [1][2][3][4][5]. One problem with these mcthods is thc complexity of the right ventricular geomctry, which Icads to an overemphasis on the local conditions in the close vicinity of the electrodes.…”
Section: Imroih'ctionmentioning
confidence: 99%
“…Intracaacdiac impedance measurement was initially developed as a volume measurement technique (RUSHMER, 1953;GEDDES et al, 1966;KUBIECK, 1966) and later as a haemodynamic sensor 1986;McKAY et al, 1984). Multiple studies have demonstrated the relationship between stroke volume and changes in impedance during systole and diastole of the ventricles (RUSHMER, 1953;GEDDES et al, 1966;KUBIECK, 1966;SALO et al, 1984;1986;MCKAY et al, 1984;CHIRIFE et al, 1993).…”
Section: Introductionmentioning
confidence: 97%